Effect Of V Arious Type Of Gelucire On The Sustained Release Performance Of Calcium Alginate Bead - Abdullah Alsheikh Wace, Mohammed Ali (2009)
Natrium Alginat merupakan polimer asli yang banyak digunakan dalam industri farmaseutikal.